A Hybrid Control Problem for a Linear System with Constant Coefficients - Avetisyan, Ara S.; Shahinyan, A. S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The problem of hybrid control of a linear system movement is discussed. It isa ssumed that the coefficients of the considered system are constants. Also, it is assumed that a subsystem of our main plant satisfies some conditions. Then, some of the states in that subsystem are considered as control inputs and thus the subsystem is optimallys tabilized using LQR stabilizer. The optimal solutions of the subsystem are used as control actions on the whole system. A numerical example system is presented for which the hybrid of optimal stabilizing control actions of a subsystem and control actions for the main system is introduce. Քննարկվում է գծային համակարգի շարժման հիբրիդային կառավարման խնդիրը: Ենթադրվում է, որ դիտարկվող համակարգի գործակիցները հաստատուններ են: և մեր հիմնական կայանի ենթահամակարգը բավարարում է որոշ պայմանների. այդ ենթահամակարգի որոշ դիրքեր համարվում են որպես հսկիչ մուտքեր, և ենթահամակարգը օպտիմալորեն կայունացվում է՝ օգտագործելով LQR կայունացուցիչ: Ենթահամակարգի օպտիմալ լուծումներն օգտագործվում են որպես ղեկավարման ազդակներ ամբողջ համակարգի վրա: Ներկայացված է թվային համակարգի ղեկավարման օրինակ, որի դեպքում ներդրվում է ենթահամակարգի օպտիմալ կայունացնող ազդակների և հիմնական համակարգի ղեկավարման ազդակների հիբրիդը: Обсуждается проблема гибридного управления движением линейной системы. Предполагается, что коэффициенты рассматриваемой системы постоянны и подсистема нашего основного агрегата удовлетворяет некоторым условиям: некоторые состояния в этой подсистеме рассматриваются как управляющие входы, и, таким образом, подсистема оптимально стабилизируется с помощью стабилизатора LQR. Оптимальные решения подсистемы используются как управляющие воздействия на всю систему. Представлен численный пример системы, для которой вводится гибрид управляющих воздействий, исходящих из оптимальной стабилизации подсистемы, и управляющих воздействий на основную систему.
Keywords: Mechanics